Wpływ anoreksji (jadłowstrętu psychicznego) na zdolność osoby do zawarcia małżeństwa - Mierzejewski, Krzysztof (Ius Matrimoniale, 2012)
In clinical practice, one can notice the increasing number of people (mostly girls and young women) who come to receive treatment on account of their anorexia. This is the result of an increasing number of patients who come for treatment and better medical knowledge of this subject. A psychological eating disorder can often be difficult to recognize. Very often this disorder is accompanied by depression, fear, or a disorder of the patient’s personality. In addition, anorexia is often a symptom of a developing state of neurosis, or a very serious somatic illness which leads the body to destroy itself. This article concerns the problem of the ability of a person who has succumbed to anorexia to contract a canonical marriage. The study begins with a consideration of Canon 1095 n. 3 of the code of Canon Law. Special attention has been given to the problem of entering into relations within the personal marital community, and also the welfare of any children and the spouses in the context of anorexia. This article is intended to help in the legal processes undertaken by the Church’s tribunals, to which comes the person who is suffering from psychological anorexia.